Higher Education Dashboard Implementation Using Data Mining and Data Warehouse: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2022)
Most of the activities including lecturer  recruiting, advertising, pupil admittance, scholar registration, educational procedures, and alumni system,  most higher education institutions now use integrated  information systems. The higher education information  system produces a lot of transactional information, and the  quantity of data is growing every day, nonetheless the best  way to utilize it is yet unknown. Each piece of data saved  on a data storage medium is used for a certain purpose. A  higher education institution, on the other hand, requires a  comprehensive understanding of all data. In light of these  circumstances, an analytical tool is required to excerpt statistics and uncover useful knowledge from large amounts  of data. Such procedures necessitate a longer processing  time and a more complicated procedure. The goal of this  study was to create a data warehouse model and dashboard  for an analytical tool, as well as to apply data mining  techniques to higher education institutions. The study  approach started with the creation of knowledge  requirements, followed by the creation of an evolutional archetype to a data warehouse, the application of data  mining methods, and the creation of a console for an  investigative utilities. The end consequence was basically a  prototype of data mining, data warehouse, and systematic utility for higher education institutions that would help  them enhance their analytical and decision-making  processes and therefore improve their performance.
Keywords: Analytic Tools; Dashboard; Data Mining; Data Warehouse; Higher Education